(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the prevalence of internet addiction in medical students com at Hanoi Medical University in 2023 and to identify factors related to internet addiction. Methods: A Cross-sectional descriptive study was used on 394 students at Hanoi Medical University. Data were collected by questionnaire and by using the short version of the internet addiction assessment scale (s-IAT) which consist of 12 standardized in Vietnam. Results: The rate of internet addiction among the 394 students was 20.8%. The condition of internet addiction in students with average or poor academic performance was higher compared to those with excellent or good grades (respectively, excellent 11.1%; good 11.4%; fair 16.7%; average 28.2%; poor 55.6%, p = 0.004). Compared to the group with internet addiction, the group without internet addiction tends to have study planning habits (p < 0.001) and read books in their free time (p = 0.023). For the groups that only study close to the exam period, there is a higher likelihood of internet addiction compared to the others (p = 0.011). Conclusion: The study shows that the rate of internet addiction among Hanoi medical students is quite low (20.8%). Factors such as year of study, academic performance, and having a study plan contribute to internet addiction.